Utilization of fermented rice straw as substitution of elephant grass in cow feed - Antonius . (Indonesian Center for Animal Research and Development (ICARD), 2009)
The objective of this research was to evaluate the use of fermented rice straw by probion on feed consumption, digestibility, daily gain and feed efficiency of Simmental cow. This study was carried out based on completely randomized design, with here dietary treatments and four replications for each treatment. The treatments were R1 (JP-15) = 40% elephant grass + 15% untreated rice straw + 45% concentrate; R2 (JPF-15) = 40% elephant grass + 15% fermented rice straw + 45% concentrate; and R3 (JPF-35) = 20% elephant grass + 35% fermented rice straw + 45% concentrate. Concentrate was given at around 08:00 while unfermented/fermented rice straw was given afterward at around 09:00. Chopped elephant grass was given twice a day at 11:00 and 16:00. Water was available through out the day. Observation was done for two months on feed consumption, digestibility, daily gain and feed efficiency. The results did not show significant differences on feed consumption, digestibility, daily gain and feed efficiency, except on digestibilities of cellulose and hemicelulose. The digestibilities of cellulose and hemicelulose of treatment R3 was higher than that of R1 and R2. It is concluded that fermented rice straw is suggested to be used as an alternative feed to substitute elephant grass in maintaining feed consumption, digestibility, daily gain and feed efficiency of Simmental cow. Key words: Probion, Cow, Rice Straw